2013
DOI: 10.1007/s10482-013-0048-5
|View full text |Cite
|
Sign up to set email alerts
|

Wohlfahrtiimonas larvae sp. nov., isolated from the larval gut of Hermetia illucens (Diptera: Stratiomyidae)

Abstract: A novel, Gram-negative, facultative anaerobic, motile and short rod-shaped bacterium, strain KBL006(T) was isolated from the larval gut of Hermetia illucens, Black soldier fly. The 16S rRNA gene sequence of strain KBL006(T) showed 96.4 % similarity to that of Wohlfahrtiimonas chitiniclastica S5(T). Strain KBL006(T) grew optimally at 30 °C, at pH 8.0 and in the presence of 1-2 % (w/v) NaCl. Oxidase activity and catalase activity were positive. The major fatty acids were C18:1 ω7c, C14:0, and C16:0. The major re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…OTUs representing the Xanthomonadaceae in the hindgut were related to the aerobic I. larvae isolated from sarcophagid flies and hematophagous mites3435, and these have been detected in other Silphidae species14. Such microbes could promote carcass digestion by producing esterase, lipase and urease activities in the hindgut3637. The obligate or facultative anaerobic Firmicutes ( Tissierella , Clostridiales and Vagococcus ) detected in adult and larval guts and anal secretions may facilitate meat digestion, because some species within this genus can digest creatine38.…”
Section: Discussionmentioning
confidence: 99%
“…OTUs representing the Xanthomonadaceae in the hindgut were related to the aerobic I. larvae isolated from sarcophagid flies and hematophagous mites3435, and these have been detected in other Silphidae species14. Such microbes could promote carcass digestion by producing esterase, lipase and urease activities in the hindgut3637. The obligate or facultative anaerobic Firmicutes ( Tissierella , Clostridiales and Vagococcus ) detected in adult and larval guts and anal secretions may facilitate meat digestion, because some species within this genus can digest creatine38.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial OTUs responsible for driving the separation of bacterial communities between carcass stages included Vagococcus, Wohlfahrtiimonas, Vitreoscilla and Myroides . The ecological relevance of these taxa is highlighted by the observation that Wohlfahrtiimonas (Xanthomonadaceae) was also detected from several other necrophagous beetles of the family Silphidae (Kaltenpoth & Steiger, ), as well as from the guts of larval and adult flesh‐eating sarcophagid flies (Gupta et al., ) and larval guts of the detrivorous black soldier fly (Lee et al., ). The taxon is closely related to the bacterium Ignatzschineria larvae that has been isolated and characterized in sarcophagid flies and the spotted flesh fly (Gupta et al., ; Toth et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…OTUs assigned to Wohlfahrtiimonas, Providencia, Morganella and Vagococcus were consistently present in larvae, and were also detected in beetles and their secretions, but were not consistently present in untreated carcass stages or soil, indicating a parent to offspring transmission of the core microbiota via the carcass surface through the anal and oral secretions The bacterial OTUs responsible for driving the separation of bacterial communities between carcass stages included Vagococcus, Wohlfahrtiimonas, Vitreoscilla and Myroides. The ecological relevance of these taxa is highlighted by the observation that Wohlfahrtiimonas (Xanthomonadaceae) was also detected from several other necrophagous beetles of the family Silphidae (Kaltenpoth & Steiger, 2014), as well as from the guts of larval and adult flesh-eating sarcophagid flies (Gupta et al, 2014) and larval guts of the detrivorous black soldier fly (Lee et al, 2014). The taxon is closely related to the bacterium Ignatzschineria larvae that has been isolated and characterized in sarcophagid flies and the spotted flesh fly (Gupta et al, 2011;Toth et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A study from South Korea reported a new Wohlfahrtiimonas sp. isolated from the larval gut of Hermetia illucens , the black soldier fly, although this fly is not pathogenic ( 6 ) . …”
mentioning
confidence: 99%